The use of assistive technology to promote practical skills in persons with autism spectrum disorder and intellectual disabilities: A systematic review - Aija Klavina; Patricia Pérez-Fuster; Jo Daems; Cecilie Nørby Lyhne; Eglantina Dervishi; Zada Pajalic; Tone Øderud; Kristin S Fuglerud; Silvana Markovska-Simoska; Tomasz Przybyla; Michal Klichowski; Gregor Stiglic; et al. (Digital Health)
Persons with autism spectrum disorder (ASD) and/or intellectual disability (ID) have difficulties in planning, organising and coping with change, which impedes the learning of daily living skills (DLSs), social participation and self-management across different environmental settings. Assistive technologies (ATs) is a broad term encompassing devices and services designed to support individuals with disabilities, and if used in a self-controlled manner, they may contribute inclusion in all domains of participation. This comprehensive literature review aims to critically assess and unify existing research that investigates the use of assistive technology within the practical domain for individuals with ASD and/or ID. The 18 relevant studies included in this review highlighted the benefits of AT for social participation and independence in daily activities of individuals with ASD and/or ID. Professionals working with this target group should be knowledgeable of the speedy progress of AT products and the potential of persons with ASD and/or ID to use mainstream devices to meet their individual needs. This awareness provides an opportunity to advocate for the universal benefits of AT for everyone. Technologies such as virtual reality, mobile applications and interactive software have been shown to improve DLSs, communication and social interaction. These tools offer engaging, user-friendly platforms that address the specific needs of these individuals, enhancing their learning and independence.